Hawaiian kiss with the brooding doc - Wilson, Scarlet (Harlequin medical romance, 2025)
Opposites attract? Living in Hawaii should be pure paradise for Dr. Piper. But while she is a ray of sunshine, her boss is proving to be a permanent rain cloud. Piper can't deny that Jamie is an exceptional doctor...nor blame him for being guarded when she's harboring a heartbreak of her own. But once Piper uncovers Jamie's reason for being the department's grouch, a surprising attraction begins to grow. Still, a relationship with him must surely stay off-limits-even after their earth-shattering kiss?